Review: Penerapan Model Pembelajaran PjBL untuk Meningkatkan Keterampilan Proses Sains dan Hasil Belajar Peserta Didik pada Mata Pelajaran Biologi - Nining Suryani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
21st-century learning is focused on the development of students' moral and intellectual character as well as various skills to face diverse challenges. One student-centered learning model is Project-Based Learning (PjBL). In project-based learning, students engage in tasks that encourage them to solve real and relevant problems within the context of the real world, rather than merely absorbing information. This research aims to analyze the application of the PjBL model in enhancing science process skills and student learning outcomes in high school biology subjects. This type of research is a literature review. The study was conducted by reviewing 20 articles from national and international scientific journals using databases such as PubMed, IEEE Xplore, Scopus, Web of Science, and Google Scholar. The keywords used in the literature search were: project-based learning, PjBL, science process skills, and learning outcomes. The results indicate that the implementation of the Project-Based Learning (PjBL) model in high school biology subjects can improve science process skills and student learning outcomes.